ANTESEDEN DAN KONSEKUENSI KEPUASAN PELANGGAN DALAM KONTEKS WORD-OF-MOUTH - Sukaris sukaris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
The purpose of this study is to analyze the antecedents and consequences of customer satisfaction in context of Word-of-Mouth. Data was collected through quizzes from